A Scoping Review Exploring Access to Survivorship Care for Childhood, Adolescent, and Young Adult Cancer Survivors: How Can We Optimize Care Pathways? - McLoone JK; Sansom-Daly UM; Paglia A; Chia J; Larsen HB; Fern LA; Cohn RJ; Signorelli C (Dove Medical Press, 2023)
Jordana K McLoone,1,2 Ursula M Sansom-Daly,1,2 Alexia Paglia,1,2 Jessica Chia,1,2 Hanne Bækgaard Larsen,3 Lorna A Fern,4 Richard J Cohn,1,2 Christina Signorelli1,2 1Behavioural Sciences Unit, Discipline of Paediatrics & Child Health, School of Clinical Medicine, UNSW Medicine & Health, Randwick Clinical Campus, UNSW Sydney, Sydney, NSW, Australia; 2Kids Cancer Centre, Sydney Children's Hospital, Randwick, NSW, Australia; 3Department for Pediatric and Adolescent Medicine, The Juliane Marie Center, Copenhagen University Hospital-Rigshospitalet, Copenhagen, Denmark & Faculty of Health and Medical Sciences, University of Copenhagen, Copenhagen, Denmark; 4Cancer Clinical Trials Unit, University College London Hospitals NHS Foundation Trust, London, NW1 2PG, UKCorrespondence: Jordana K McLoone, Discipline of Paediatrics & Child Health, UNSW Medicine & Health, Randwick Clinical Campus, UNSW, Sydney, NSW, Australia, Email J.McLoone@unsw.edu.auAbstract: Childhood, adolescent, and young adult (CAYA) cancer survivors are at risk of developing late effects associated with their cancer and its treatment. Survivors' engagement with recommended follow-up care to minimize these risks is suboptimal, with many barriers commonly reported. This scoping review aims to summarize the barriers to accessing follow-up care, using the dimensions of Levesque's framework for accessing healthcare. We retrieved quantitative studies addressing barriers and facilitators to accessing survivorship care in CAYA survivors from PubMed, EMBASE and CINAHL. Data was categorized into the five healthcare access dimensions outlined in Levesque's framework: i) approachability, ii) acceptability, iii) availability and accommodation, iv) affordability, and v) appropriateness. We identified 27 quantitative studies in our review. Commonly reported barriers to accessing care included a lack of survivor and provider knowledge of cancer survivorship, poor health beliefs, low personal salience to engage in follow-up care, high out-of-pocket costs and survivors living long distances from clinical services. Many studies reported increased barriers to care during the transition from paediatric to adult-oriented healthcare services, including a lack of developmentally appropriate services, lack of appointment reminders, and a poorly defined transition process. Healthcare-related self-efficacy was identified as an important facilitator to accessing follow-up care. The transition from pediatric to adult-oriented healthcare services is a challenging time for childhood, adolescent, and young adult cancer survivors. Optimizing CAYAs' ability to access high-quality survivorship care thus requires careful consideration of the quality and acceptability of services, alongside financial and physical/practical barriers (eg distance from available services, appointment-booking mechanisms). Levesque's model highlighted several areas where evidence is well established (eg financial barriers) or lacking (eg factors associated with engagement in follow-up care) which are useful to understand barriers and facilitators that impact access to survivorship for CAYA cancer survivors, as well as guiding areas for further evaluation.Keywords: pediatric, adolescent and young adult, cancer, survivorship care, barriers, access to care